Targeting Multicopy Prophage Genes for the Increased Detection of Borrelia burgdorferi Sensu Lato (s.l.), the Causative Agents of Lyme Disease, in Blood - Shan, Jinyu; Jia, Ying; Teulières, Louis; Patel, Faizal; Clokie, Martha R. J. (Frontiers in Microbiology, 2021)
The successful treatment of Lyme disease (LD) is contingent on accurate diagnosis. However, current laboratory detection assays lack sensitivity in the early stages of the disease. Because delayed diagnosis of LD incurs high healthcare costs and great suffering, new highly sensitive tests are in need. To overcome these challenges, we developed an internally-controlled quantitative PCR (Ter-qPCR) that targets the multicopy terminase large subunit (terL) gene encoded by prophages that are only found in LD-causing bacteria. The terL protein helps phages pack their DNA. Strikingly, the detection limit of the Ter-qPCR was analytically estimated to be 22 copies and one bacterial cell in bacteria spiked blood. Furthermore, significant quantitative differences was observed in terms of the amount of terL detected in healthy individuals and patients with either early or late disease. Together, the data suggests that the prophage-targeting PCR has significant power to improve success detection for LD. After rigorous clinical validation, this new test could deliver a step-change in the detection of LD. Prophage encoded markers are prevalent in many other pathogenic bacteria rendering this approach highly applicable to bacterial identification in general.